Best Practices for Creating and Conducting Educational Escape Rooms: A Comprehensive Guide for Teachers - Gordillo Méndez, Aldo; Santamaría Urbieta, Alexandra; López-Pernas, Sonsoles; Gutiérrez Gómez-Calcerrada, Sonia; Milošević, Miljan; Ćosić, Maja; Barra Arias, Enrique; Elmoazen, Ramy (Universidad Politécnica de Madrid, 2026)
[Resumen no disponible]
The objective of this document, titled “Best Practices for Creating and Conducting Educational Escape Rooms: A Comprehensive Guide for Teachers” (or “IGLUE Best Practices” for short), is to present guidelines and recommendations for helping teachers of any educational level and knowledge area to design, build, execute, and evaluate educational escape rooms considering different formats (physical, virtual, and hybrid) and delivery modes (face-to-face and remote). The guidelines and recommendations defined in this document (also referred to as practices) cover the whole life cycle of educational escape rooms and have been organised according to the phases of this cycle: design, build, execution, and evaluation.
Keywords: game-based learning; gamification; educational escape rooms; breakout games; technology-enhanced learning; active learning; teaching practices